2023
DOI: 10.1002/dta.3455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HepG2 cell 3D cultivation on the metabolism of the anabolic androgenic steroid metandienone

Abstract: The elucidation of the metabolic fate of prohibited substances is crucial for the abuse detection. The human hepatocyte cell line HepG2 can be used to study biotransformation. In order to improve this in vitro model system, we compared the HepG2 spheroid generation using three different techniques: a forced floating, a scaffold‐free and a scaffold‐based method. We characterized the spheroids with regard to the expression levels of the proliferation marker Mki67, the liver‐specific marker albumin and biotransfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For instance, Gronert et al assessed the utility of an in vitro model, exploiting a human hepatocellular carcinoma cell line (Hep G2) cultivated into spheroids, in mimicking the in vivo metabolism of AAS 125 . In a proof‐of‐principle study, the viability of spheroids and their potential to biotransform an AAS into known (long‐term) metabolites was demonstrated by means of metandienone, with the experimental conditions showing best results when scaffold‐based 3D cultivation of spheroids was employed.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…For instance, Gronert et al assessed the utility of an in vitro model, exploiting a human hepatocellular carcinoma cell line (Hep G2) cultivated into spheroids, in mimicking the in vivo metabolism of AAS 125 . In a proof‐of‐principle study, the viability of spheroids and their potential to biotransform an AAS into known (long‐term) metabolites was demonstrated by means of metandienone, with the experimental conditions showing best results when scaffold‐based 3D cultivation of spheroids was employed.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Investigating and revisiting the metabolic fate of doping agents is vital for comprehensive sports drug testing methods as well as subsequent result interpretation. Both in vitro and in vivo approaches assisting in studying biotransformation reactions have been shown to provide particularly useful tools as demonstrated by means of 3D‐cultivated HepG2 cells and rat administration studies using the anabolic‐androgenic steroids (AAS) metandienone 4 and boldenone 5 . With sulfo‐conjugated phase‐II metabolites of these and other AAS receiving growing attention in routine doping controls, investigating their analytical behavior on existing testing platforms has become essential, particularly by assessing the applicability of analytical platforms commonly available in anti‐doping laboratories to such metabolic products 6 .…”
mentioning
confidence: 99%
“…The human hepatic HepG2 cell line was chosen for the initial investigation of the postulated presence of metabolites with an 17,17-dimethyl-18-nor-Δ13 structure with targeted GC-MS/ (MS) analysis. This cell line has already been used as an in vitro model in the metabolism study of AASs, like testosterone, [38][39][40] methandienone, 40,41 epitestosterone, 4-chlorotestosterone, and methyltestosterone. 42 Once the research hypothesis was confirmed F I G U R E 2 Hypothetical metabolic transformation of methyltestosterone to 17,17-dimethyl-18-nor-5α-androst-13-en-3z-ol and 17,17-dimethyl-18-nor-5β-androst-13-en-3z-ol metabolites.…”
mentioning
confidence: 99%